School based health workers in Nepal: Supporting evidence based decision making. (2018)
SUMMARY: Background and Aim: There is a dilemma of whether and how health workers can be mobilized in a school setting in terms of insuring health and well being of school children in Nepal. Therefore, we conducted a rapid review of existing systematic reviews to develop strategies to mobilize health workers in schools. We also aimed to explain the local applicability of the intervention strategies, using local evidence, to support policy makers better implement the interventions in Nepal. Methods: A systematic search for systematic reviews that explained the effect of health interventions at school to produce various health outcomes among the school children. Data synthesis and analysis included line by line coding of the extracted data and development of themes. Relationships between themes were sought and that led to the identification of intervention strategies and generative mechanisms. Finally, the strategies and mechanisms were refined based on the local evidence from Nepal. Findings: Our synthesis revealed five major intervention strategies, in which a health worker can be mobilized. These are: awareness raising; behavior change; health service provision; support provision; and community engagement strategies. Likewise, our synthesis identified three major pathways on how behavior change can be produced via mobilizing health workers. First, health workers can contribute to changing health related knowledge and behaviors of school children. Second, health workers can contribute to increasing self-efficacy for behavior change especially for vulnerable children. Finally, a health worker can contribute to reducing social barriers for self efficacy and behavior change among school children. Conclusions: This synthesis provides a program theory illustrating a more detailed picture of contextual factors and the pathways surrounding the mobilization of health workers in a school setting. Moreover, it builds a greater understanding of the mechanisms that support the adaptation of intervention strategies in terms of the socio-structural and cultural context in Nepal. The envisioned provision of school based dedicated health worker has the opportunity to improve health and academic outcome of children in Nepal. This study reviewed the available systematic reviews to assess the effectiveness of school based health interventions with the provision of health workers in school setting.